2021
DOI: 10.5937/ekopre2103243s
|View full text |Cite
|
Sign up to set email alerts
|

Serbian economy recovery in the post COVID-19 era: Cluster approach

Abstract: The COVID-19 crisis differs from previous ones. It disrupts global value chains, redirects business toward regional cooperation in a highly globalized world, and forces new business model development toward digitalization. This crisis affected both supplyand demand-side and all countries worldwide, regardless of their economic strength. To support economic recovery, while at the same time fighting for health system endurance through lockdowns and prevention measures, economic decision-makers all around the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Further, Millaku et al (2021) confirmed that the prioritization of fiscal reforms had an effect on tourism recovery measures in Kosovo during the post COVID era. Savić et al (2021) noted that fiscal policy was important in recovering tourism demand in the short-run. However, according to AZMI et al (2021) in order to stabilize the effects of the fiscal impacts in the long-run, there is need to sustain the income generating potential of the nation.…”
Section: Literature Review and Theoretical Implicationsmentioning
confidence: 99%
“…Further, Millaku et al (2021) confirmed that the prioritization of fiscal reforms had an effect on tourism recovery measures in Kosovo during the post COVID era. Savić et al (2021) noted that fiscal policy was important in recovering tourism demand in the short-run. However, according to AZMI et al (2021) in order to stabilize the effects of the fiscal impacts in the long-run, there is need to sustain the income generating potential of the nation.…”
Section: Literature Review and Theoretical Implicationsmentioning
confidence: 99%
“…In terms of inflation, the NBS was much more prepared in 2020 than in 2008 when inflation was around 14%. In line with other world economies, the NBS has begun to implement an expansionary monetary policy in terms of the inherent lowering of interest rates in the initial periods of the pandemic (Savić et al, 2021). The transition from disciplined monetary policy to a regime of strict expansion is shown in the context of three sets of monetary measures: (i) liquidity control measures; (ii) direct aid measures; (iii) reactions to supply and demand shocks (Narodna Banka Srbije, 2021).…”
Section: Comparative Covid-19 Approachmentioning
confidence: 99%
“…As the link between exports and economic growth is two-way (Syamni, 2021), countries with a high share of tourism, as well as some industrialized countries, have faced negative growth rates. On the other hand, the Republic of Serbia in 2020 achieved a decline in gross domestic product of only 1.1%, which is one of the better results given the European countries (Savić et al, 2021). This is the result of a well-conducted macroeconomic policy, timely and effective measures to overcome the consequences of the crisis, but also above-average results in certain sectors of the economy.…”
Section: Introductionmentioning
confidence: 99%